PENDEKATAN SATUAN PANAS (HEAT UNIT) UNTUK PENENTUAN FASE PERTUMBUHAN DAN PERKEMBANGAN TANAMAN TOMAT DI DALAM RUMAH TANAMAN (GREENHOUSE) - Abd. Syakur (Agroland: Jurnal Ilmu-ilmu Pertanian, 2012)
The aim of this research was to determine heat unit (degree days) of tomato grown in a greenhouse.  Heat unit was used to determine growing and development stage of tomato.  Tomato was planted in the greenhouse during August until December 2010 at the BALITKLIMAT, Cimanggu, Bogor.  The weather data such as air temperature, minimum and maximum temperature, and relative humidity were collected using authomatical weather station (aws). Solar radiation intensity was collected using solary meter. The results of the research showed that heat unit of tomato were 1661oC days. Average of air temperature in the greenhouse was 27.1oC and average of relative humidity was 74.2% with average radiation intensity was 9.3 MJ m-2 day-1